Pilot study using the ECHO model to enhance linkage to care for patients with hepatitis C in the custodial setting. Issue 12 (8th September 2020) - Mendizabal, Manuel; Testa, Pablo; Rojas, Mercedes; Colaci, Carla S.; Elías, Solana; Nicolini, Paula; Olguín, Soledad; Dunn, Carolina; Ronchi, Claudio; Barreiro, Mariano; Zirpoli, Mercedes; Piñero, Federico; et al.
Abstract: Prisoners in most countries have a higher prevalence of HCV than the general population, but their access to treatment is very limited. Our aim was to evaluate a pilot programme using the ECHO model to enhance linkage to care in patients with HCV in 3 Argentinean prisons between October 2018 and January 2020. All inmates were invited to participate, and data were collected through a personal interview. We then estimated HCV prevalence with dried blood spot and performed a logistic regression analysis to identify risk behaviours associated with HCV infection. Finally, HCV management was assessed and monitored through ECHO. Overall, 1141 inmates agreed to participate, representing 39.7% of the total prison population. Anti‐HCV prevalence was estimated at 1.58% (CI 0.93; 2.48), being significantly higher in women 2.98% (CI 1.4;5.6) than in men 1.07% (CI 0.5; 2.0); P = .03. Patients with anti‐HCV were significantly older than those who tested negative, 42.3 years (CI 37.6;47.1) vs 30.1 years (CI 30.6;31.2), P < .001, respectively. Multiple logistic regression analysis, identified age OR 1.07 (CI 1.03;1.12, P = .001), history of sexually transmitted disease OR 3.08 (CI 0.97;9.82, P = .057) and intravenous drug use OR 12.6 (CI 3.31;48.53, P < .001) as risk factors associated with anti‐HCV. Treatment was initiated in all the patients with specialist physician support utilizing ECHO model. In conclusion, our pilot study reported a low prevalence of anti‐HCV in the studied population. Incarceration provides an ideal opportunity for testing and treating HCV. ECHO model arises as a useful tool to support assessment and treatment for inmates with chronic HCV.